Pengantar Ilmu Ekonomi Konvensional, Sistem Ekonomi, Perkembangan Pembangunan Dan Investasi Di Indonesia - Rezeki, Indah Indah (PARETO : Jurnal Ekonomi dan Kebijakan Publik, 2023)
The Indonesian economic system is used to allocate its resources to both individuals and organizations in the Indonesian state. The fundamental difference between an economic system and another is how the system regulates the production factors of a country in Indonesia. Indonesia has two economic systems, namely a planned economy and a traditional economy. Economic development aims to see the process of increasing total income (economic growth) in the country of Indonesia, by taking into account the increase in population, fundamental changes in the economic structure and income distribution. One of the economic developments is investment. . The aim of investing is to get a better life in the future, reduce inflationary pressure and save taxes. There are three types of investment in Indonesia, namely investment based on assets, influence, and form. Investments allow a person to meet his future needs by determining priority needs, making good plans and applying discipline in his company consistently.